PENGARUH PENGGUNAAN APLIKASI NEARPOD TERHADAP MINAT BELAJAR SEJARAH KELAS XI IPS SMAS MUJAHIDIN PONTIANAK - M. Yudha Al Fajar; Andang Firmansyah; Astrini Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine whether there is an effect of using the Nearpod application on the interest in learning history among Grade XI IPS students at SMAS Mujahidin Pontianak. The research method employed was a quantitative approach using a quasi-experimental design, specifically the posttest-only control group design. The population of this study consisted of all Grade XI IPS students at SMAS Mujahidin Pontianak, totaling 137 students. The sample comprised two groups, namely the experimental class and the control class, which were selected using purposive sampling techniques. Data were collected through observation, questionnaires, and documentation. The data analysis was conducted using the Mann–Whitney U test. The results of the study show that: (1) the interest in learning history of students who participated in learning using the Nearpod application was categorized as very high, with a percentage score of 81% in the experimental class; (2) the interest in learning history of students who participated in learning without using the Nearpod application was categorized as high, with a percentage score of 72% in the control class; and (3) based on the results of the Mann–Whitney U test, a significant value (2-tailed) of 0.008 < 0.05 was obtained, along with an average percentage score of 80%. Therefore, it can be concluded that the use of the Nearpod application has a significant effect on the learning interest of Grade XI IPS students.